Social Protection And Voices From Below During The Covid-19 Pandemic In Malaysia - Por, Heong Hong (Silkworm Publisher, 2023)
In late July 2021, Malaysia was almost two months into its third nationwide lockdown to contain the COVID-19 pandemic. Twenty-seven-year-old Mohamed Ismad was struggling to make ends meet. Originating from Sabah's Sandakan, Ismad was a bachelor who had graduated from a local university in Sabah and made a living as a GrabCar driver in Kata Kinabalu. He was kept afloat by the federal government's one-time Geran Khas PRIHATIN (PRIHATIN Special Grant or GKP) RM1 1,500 cash handout. Moreover, he had to prematurely withdraw his meager savings from the Employees' Provident Fund (EPF), a retirement fund for workers in the private sector. Despite receiving state assistance, Ismad still felt the pinch. Before the pandemic, he made over RM 3,000 per month as a GrabCar driver, but his income was almost halved to about RM 1,800 per month during the pandemic. Meanwhile, his personal expenses remained the same, and he began having to support his jobless and divorced mother and younger siblings in Sandakan. While the government aids have been timely, they've proven far from sufficient, as Ismad explains: